Interaksi Bakteri Antagonis dengan Tanaman: Ketahanan Terinduksi pada Tanaman Jagung - Nurasiah Djaenuddin (Puslitbang Tanaman Pangan, 2016)
Biological control against soil-borne pathogens is an option to reduce disease activity by pathogens through one or more resistance mechanisms. In the last two decades, interest in biological control usage against soil borne plant pathogens has increased because this approach can control disease not only solely, but can also be combined with other strategic control. Colonization of plant roots is an important step for soil borne pathogens and beneficial bacteria (bacterial antagonists and rhizobacteria). Colonization patterns indicate that rhizobacteria act as a biocontrol agent or as a growth promoter bacteria formation of microcolonies. Microcolonies are used as the media for bacteria to interact one with another in order to effectively coincide with the root exudates. Elicitation or the process of adding elicitor (chemical compounds) in the plant cell is aimed to induce and enhance the establishment of secondary metabolites, initially shown by Pseudomonas spp. and other gram-negative bacteria. Some strains of the species Bacillus subtilis, B. cereus and B. pumilus elicit significantly the incidence or severity of various diseases in a variety of host plants. Elicitation of systemic induced resistance by these strains is shown in experiments in the greenhouse or in the field on maize, rice, tomatoes, watermelon, and cucumber. Elicitation by Bacillus spp. wasreported to establish induced systemic resistance mechanisms in plants affected by leaf spot fungus and bacteria, viruses, nematodes, damping off and blight disease. With the advancement of this knowledge, one can explore strains of bacterial species efficiently use as advantageous agents in biological control strategy.